Strategic Speech Act Deployment in Political Debates: A Comparative Pragmatic Study of Indonesian and UK Discourse - Astutie, Riza (Indonesian Scientific Publication, 2024)
This study investigates the comparative realization of commissive and directive speech acts in political debates, focusing on Indonesian presidential discourse and UK parliamentary opposition speech. Drawing from two annotated corpora comprising approximately 500 utterances each, the research applies Searle’s speech act taxonomy to analyze how speech acts are distributed and realized across political roles and contexts. Using manual annotation supported by ELAN, combined with frequency analysis and qualitative discourse methods, the study finds that commissive acts are predominantly employed by incumbent speakers to promise policy actions and build credibility, whereas opposition figures favor directive acts to challenge, question, and demand accountability. Lexical markers such as “promise,” “guarantee,” and “must” serve as reliable indicators for classifying speech acts. The analysis reveals that speech act usage is not only influenced by speaker role but also shaped by debate phase and cultural-political context. Commissives cluster around opening and closing phases, while directives dominate in rebuttals. These findings reflect role-based strategic communication choices and underscore the pragmatic flexibility political speakers must maintain across different institutional settings. The study contributes to political pragmatics by offering cross-contextual insights into how language functions strategically in political discourse. It calls for broader multilingual corpora and refined speech act models that account for both cultural norms and communicative intent.